AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN KUNYIT (Curcuma longa LINN.) TERHADAP JAMUR Candida albicans - Pulungan, Ahmad Shafwan S (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
The potential of Plant as one alternative medicine has been explored. One of the plants that have potential as a drug in inhibiting the fungus is a turmeric leaf. Turmeric leaf have secondary metabolite such as flavonoid, steorid, curcumin, essential oils, tannins. Secondary metabolite are thought to have the ability to inhibit the growth of the Candida albicans. Ethanol extract turmeric leaves used of concentration 10%, 20%, 30%, 40%, 50% and 60%. Each concentration after being tested to Candida albicans has different capabilities in inhibiting fungal growth. The best concentration in inhibiting fungal growth is a concentration of 60% with a mean diameter of the inhibit zone by 7.47 mm. Inhibitor zone that is formed belongs to the medium category. The result obtained showed the higher concentration of ethanol extract of turmeric leaf the the ability to inhibit the groeth of fungis is also getting bigger.